Expansion of the genome editing toolbox of Clostridium autoethanogenum - Seys, François M. (2022)
Current environmental crises – from rising global temperatures to biodiversity collapse – have created an urgent need for new, circular and sustainable ways of producing and recycling materials and energy independently of fossil resources. Gas fermentation, by consuming greenhouse gases to produce fuels and chemicals, offers human society an attractive route to sustainability. This thesis describes the development of genome editing tools to facilitate the engineering of the gas fermenting Clostridium autoethanogenum.